Activation of dissolved molecular oxygen by Cu(0) for bisphenol a degradation: Role of Cu(0) and formation of reactive oxygen species. (February 2020) - Long, Jiajun; Xu, Longqian; Zhao, Linghui; Chu, Huaqiang; Mao, Yunfeng; Wu, Deli
Abstract: In this study, Cu(0) was synthesized with NaBH4 as a reducing agent for Cu(II) and used to activate dissolved molecular oxygen (O2 ) under acidic conditions. The Cu(0) synthesized had much higher activity than the purchased. The roles of Cu was clarified and the formation of reactive oxygen species was discussed through direct detection for the first time. By detecting the valence change of Cu in a CuO system, Bisphenol A (BPA) was found to accelerate the transformation of Cu(II) to Cu(I). Besides, the evidence from electron spin resonance (ESR) studies and scavenging tests revealed the new roles of Cu(0) that Cu(0) could not only convert O2 to produce ·O2 −, but also catalyze H2 O2 to ·OH. The results from this study offer evidence of new reaction pathways in Cu-activated O2 systems and deepen understanding of the reaction between Cu species and O2 . Highlights: BPA was oxidized by ·OH generated from Cu(0) activating O2 in acidic conditions. ·OH generation mainly took place on Cu surface. The complex of BPA on Cu surface promoted Cu(II) converting to Cu(I). ·OH can be produced through Cu(0) catalyzing H2 O2 .